2019
DOI: 10.1186/s12889-019-6920-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing awareness of healthcare providers on maternal sepsis: a mixed-methods approach

Abstract: Background An awareness campaign set to accompany the Global Maternal Sepsis Study (GLOSS) was launched in 2017. In order to better develop and evaluate the campaign, we sought to understand the factors that influence awareness of maternal sepsis by exploring healthcare providers’ knowledge, perception of enabling environments, and perception of severity of maternal sepsis. Methods We used a mixed-methods approach that included 13 semi-structured interviews to GLOSS reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
1
Order By: Relevance
“…All Likert scale answers were dichotomised assigning a 1 to the two most favourable responses (ie, they felt very or somewhat confident about making the right decision) and 0 to the combination of remaining options (neutral, not very confident or not confident at all). While previously we assessed dichotomisation using 1 to the single most favourable response (ie, respondent felt very confident) and a 0 to the combination of remaining options (somewhat confident, neutral, not very confident or not confident at all) 23 we decided to include a more flexible definition of confidence, perception of availability of resources and feeling of support to allow for a more robust denominator that would enable comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All Likert scale answers were dichotomised assigning a 1 to the two most favourable responses (ie, they felt very or somewhat confident about making the right decision) and 0 to the combination of remaining options (neutral, not very confident or not confident at all). While previously we assessed dichotomisation using 1 to the single most favourable response (ie, respondent felt very confident) and a 0 to the combination of remaining options (somewhat confident, neutral, not very confident or not confident at all) 23 we decided to include a more flexible definition of confidence, perception of availability of resources and feeling of support to allow for a more robust denominator that would enable comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the definition used for awareness for this campaign, survey formulation and dissemination, including analysis of baseline data, have been published elsewhere. 23 Briefly, a precampaign 32-question survey was developed to gather baseline information on healthcare providers' awareness of maternal sepsis through self-reported knowledge on maternal sepsis and perception of their work environments as enabling for the identification and management of maternal sepsis. Knowledge was assessed through questions relating to whether respondents had heard of maternal sepsis, correct identification of criteria that define maternal sepsis (infection plus organ dysfunction) and identification of correct initial management of maternal sepsis and infections (antibiotics and fluids) when maternal sepsis was suspected in the case vignette presented in the survey.…”
Section: Evaluation Of the Stop Sepsis! Awareness Campaignmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants reported implementing changes in how they managed women with infection and sepsis as a result of their participation in GLOSS. Some of these changes could be expected, to some extent, as GLOSS included a campaign aimed at increasing awareness among healthcare providers working in GLOSS participating facilities [ 19 ]. Some studies have shown that the action of conducting research could be an intervention in and of itself, as participation in research can increase awareness on the topic of interest and, therefore, bring about improvements in how patients are cared for [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30] Awareness among clinicians of sepsis might lead to early diagnosis and effective management of sepsis. 6,31 A long road lies ahead in this battle against maternal sepsis due to the ever-evolving and new data available. Antibiotic stewardship can help in the judicious use of antibiotics and combat antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%